Predicting the oil contents in sunflower genotype seeds using near-infrared reflectance (NIR) spectroscopy. - GRUNVALD, A. K. (2014)
ABSTRACT: The aim of this experiment was to calibrate the NIR spectroscopy equation to evaluate the oil content of sunflower seeds from different genotypes produced under different environmental conditions in Brazil. The spectra of 901 standard samples obtained from 88 hybrids and 116 lines, which were evaluated in 11 locations, were collected from intact seeds (achenes) and correlated with data generated by nuclear magnetic resonance analysis. The calibration was determined by linear regression using partial least squares to estimate the parameters. The goodness of fit was evaluated using the coefficient of determination (R2), standard error of calibration (SEC) and the standard error of performance (SEP). The wavelengths ranging from 1319 to 1760 nm were selected for the calibration. The R2 was 0.87, the SEC was 2.39, and the SEP was 1.97. The oil content values obtained for the 19 hybrid seeds analyzed by NIR spectroscopy that were not included in the calibration were similar to the values obtained using the chemical method. The similarities between the values obtained using both methods and the R2, SEC and SEP values indicated that it is possible to establish a calibration equation using NIR spectroscopy to determine the oil contents of sunflower seeds produced under Brazilian field conditions. RESUMO: O objetivo desse trabalho foi estabelecer uma equação de calibração pela análise da espectroscopia de NIR para a avaliação dos teores de óleo em sementes de genótipos de girassol obtidas em condições ambientais brasileiras. Os espectros de 901 amostras padrões, provenientes de 88 híbridos e 116 linhagens avaliados em 11 localidades, foram coletados de aquênios intactos e correlacionados com os valores de óleo obtidos por análise de ressonância magnética nuclear. A equação de calibração foi determinada por regressão linear, cujos parâmetros foram estimados pelo método de mínimos quadrados parciais. A precisão foi verificada pelo coeficiente de determinação (R2), erro padrão de calibração (SEC) e pelo erro padrão de desempenho (SEP). A região de comprimento de onda entre 1319 e 1760 nm foi selecionada para a calibração. O R2 foi 0,87, o SEC foi 2,39 e o SEP foi de 1,97. Adicionalmente, a análise do teor de óleo pelo NIR de 19 híbridos não incluídos na calibração foi similar aos valores obtidos no método químico padrão. Esta similaridade e os valores de R2, SEC e SEP possibilitaram inferir que é possível estabelecer uma equação de calibração pela espectroscopia de NIR para a avaliação do teor de óleo em sementes de genótipos de girassol cultivados em condições ambientais brasileiras.